Africa Digest : Trends and issues in business Vol. 10 - Burger, Johan (2020)
The Africa Digest is a fortnightly e-newsletter scanning the key trends in the macro-environment and industry to promote knowledge and raise understanding of business in Africa. This issue explores: 1. Trends of China in Africa - This month’s scans of events related to China reveal continuing trends and highlight several new angles. We see China and India heating up their competition on the African continent. Notably, China continues to target the continent with its low cost smart phone. 2. Trends in Financial Services - Companies expanding into Africa often have to form banking relationships with institutions on the continent. Their home country banks frequently appear hesitant to support their expansion drives into Africa. On the continent itself, some struggling banks have become acquisition targets. Stronger local banks, by acquiring their weaker peers, are emerging as pan-African banks. 3. Trends in Investments and Economics - Investments in Africa continue to emerge, with various countries outside the continent targeting countries in Africa such as Egypt, Nigeria and South Africa. In spite of the perceived risks, FDI into Africa continues at a brisk rate. Various factors are supporting this phenomenon. Unfortunately, it does seem some factors are moving a number of the oil majors to look elsewhere for revenue growth. 4. Trends of Japan in Africa - Japan realizes they were very slow to get involved in Africa. Once they made the decision to invest, they intend to stay and to be in the continent for the long haul. Japan’s involvement in Africa is not new, however. Japan’s government launched the Tokyo International Conference of African Development (TICAD) in 1993. Its mission is to promote Africa's development, peace and security, through strengthening of relations in multilateral cooperation and partnership with Japan. In recent years, it is clear that Japanese companies are becoming more prominent in Africa. 5. Southeast Asia in Africa - Southeast Asia has been involved in Africa for some time. Although companies from these countries can tap opportunities in ASEAN, some have elected to move further abroad to Africa, despite the perceived risks. ASEAN governments also support investments into Africa. These investments take place over a broad range of industries.